The Effect of Distance Education: A Meta-Analytic Assessment of Simonson's Equity Theory based on Synchronous and Asynchronous - Roger S. Bensilva; Phill F. Abraham; Annie Y. William (Universitas Nurul Jadid Probolinggo, Indonesia, 2022)
Simonson, Schlosser and Hanson (1999) argue that a new theory called “equivalency theory” is needed to account for the unique features of the “teleconferencing” (synchronous) model of DE that is prevalent in many North American universities. Based on a comprehensive meta-analysis of the comparative literature of DE (Bernard, Abrami, Lou, Wozney, Borokhovski, Wallet, Wade, Fiset, & Huang, in press), we are able to assess empirically whether equivalency has been achieved in prior comparative DE research. This paper includes a brief summary of the results of the split between synchronous and asynchronous patterns of DE, and addresses the implications these data have for developing separate theories of DE for synchronous (i.e., group-based) and asynchronous (i.e., individualized) applications. We examine data based on achievement, attitude and retention outcomes and coded study features (i.e., methodological, pedagogical and media) relating to them.